Analysis of the perception of the effort in front crawl and breaststroke swimming - Invernizzi, P. L.; Michielon, G.; Longo, S.; Scurati, R. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Fatigue is generally defined as a decreased performance due to physiological or psychological limitations. Among them, the intensity and the duration of the exercise and the conscious perception of the effort are very relevant. CR10 scale (Borg, 1982) is useful to measure the perception of the effort during the exercise. This study aimed to assess some subjective features of the perception of effort in breaststroke and front crawl swimming. Methods: Ten swimmers (18.2±0.2 years, 67.9±3.6 kg, 180±1.0 cm, 21.07±0.66 kg/m2) participated in the study. Swimmers were asked to perform 50, 100 and 200 meters front crawl (FC) and breaststroke (BR), at the maximum velocity. The subjective perceptions of the general, muscular and respiratory efforts were assessed through the CR10 scale and compared with respect to the distance and to the swimming technique. Results: The perception of the effort was higher (p<0.001) after the trial on 100m than after the trial on 50m, both in front crawl and breaststroke (AU±SD; general effort: 6.70±1.34 vs. 4.00±0.94 and 8.20±0.79 vs. 3.70±1.16; muscular effort: 6.30±0.95 vs. 3.05±0.90 and 7.50±1.08 vs. 3.90±1.37; respiratory effort: 6.20±1.48 vs. 3.80±1.01 and 7.40±1.17 vs. 3.80±1.03, FC and BR, respectively). The perception of the effort surveyed after the trial on 100m did not differ with respect to the trial on 200m. In the between-technique comparison of the general perception of the effort, CR10 showed lower values in FC than in BR after the 100m trial (p<0.05, 6.70±1.34 vs. 8.20±0.79, AU±SD). The perception of the muscular effort was also lower in FC than in BR, but only after the 50m trial (p<0.05, 3.05±0.90 vs. 3.90±1.37, AU±SD). No difference was found between FR and BR in the respiratory effort, in all trials. Discussion: In front crawl and in breaststroke, the distance seems to have the same effect on the perception of the general, muscular and respiratory effort, measured by CR10 scale. However, these differences are noticeable only comparing the efforts between 50m and 100m. Moreover, even if the energetic demand of front crawl and breaststroke are quite different (Capelli et al, 1998), the participants of the present study seemed to perceive only partially this difference in the general and in the muscular effort perception (in 100m and 50m trials, respectively). In the respiratory effort, subjects scarcely discriminate between the techniques, as expected from the literature.